A study of trends and factors associated with therapeutic drug monitoring (TDM) implementation for arbekacin treatment using a large Japanese medical claims database. Issue 9 (September 2022) - Ito, Saki; Goto, Ryota; Inose, Ryo; Kusama, Yoshiki; Ono, Akane; Koizumi, Ryuji; Ishikane, Masahiro; Ohmagari, Norio; Muraki, Yuichi
Abstract: Introduction: Reimbursements for pharmacist interventions and infectious disease teams have recently been introduced in Japan. Arbekacin (ABK) is used to treat pneumonia and sepsis caused by methicillin-resistant Staphylococcus aureus, and therapeutic drug monitoring (TDM) is recommended. This study aimed to clarify the trend in TDM implementation for ABK over time and the factors associated with TDM implementation using a claims database. Methods: Data of patients aged ≥15 years who received ABK for ≥3 consecutive days between 2010 and 2019 were extracted from a large Japanese medical claims database. The proportion of reimbursements claimed for TDM, pharmacist interventions, and the setup of infectious disease teams for each year were calculated. The factors associated with TDM implementation were identified using multivariate logistic regression analysis. Results: The proportion of TDM implementation for ABK increased by 9.1% from 2010 to 2019, but it remained less than 40% throughout this period. The proportion of TDM implementation was higher in patients who claimed reimbursements for pharmacist interventions than in patients who did not. Logistic regression analysis showed that the stationing of pharmacists in wards and long-term ABK treatment were significantly associated with TDM implementation. Conclusions: From 2010 to 2019, the proportion of TDM implementation for ABK was significantly low. Moreover, the factors associated with TDM implementation were clarified. An environment wherein pharmacists can help implement TDM for patients receiving ABK would be beneficial.